The Power to Pass on Taxes - A Test for Tax Shifting Based on Observables - Mario Jametti; Agustin Redonda; Anindya Sen (Center for Economic Studies and ifo Institute (CESifo), 2013)
Since gasoline has a relatively inelastic demand, raising government revenue via gasoline taxes could appear appropriate as it entails a relatively small deadweight loss. However, gasoline retail is generally a highly concentrated market, hence the assumption of perfect competition when considering tax incidence might be misleading. Theoretically, in oligopolistic markets taxes can be shifted forward less (more) than proportionally to retail prices; a possibility usually denoted by undershifting (overshifting). Generally, this depends on unobservable parameters of the demand and cost functions. In this paper we device a novel empirical test, based on observables, to assess whether taxes are under- or overshifted in an oligopolistic market. The test depends on the interaction between market structure and taxes. We apply our test to the Canadian retail gasoline market using a panel data set of 10 cities, finding that gasoline taxes are undershifted.
Keywords: H22; D43; L13; 330; tax incidence; pass-through; market structure